On The Intersection of Semi-Pure Subgroups of Abelian Group - Abdullal, H. M. A.; Barghooth, Luma J. (Iraqi Journal of Science, 2020)
The following question was raised by L.Fuchs: "what are the subgroups of an abelian group G that can be represented as intersections of pure subgroups of G ? . Fuchs also added that “One of my main aims is to give the answers to the above question". In this paper, we shall define new subgroups which are a family of the pure subgroups. Then we shall answer problem 2 of L.Fuchs by these semi-pure subgroups which can be represented as the intersections of pure subgroups.